Parents’ Role in Supporting Sport Achievement of Surakarta Women’s U-19 Football Club In Surakarta - Elen Yulianti; Agus Mukholid; Manshuralhudlori Manshuralhudlori (PJKR FKOR UNS, 2019)
This study is aimed to identify and describe the role of parents in supporting sport achievement of Surakarta U-19 Women’s Football Club in 2020. Descriptive quantitative method is used in this research. The data source is obtained from parents/guardians at Surakarta Women's Football Club. Those data needed in this study is the problematic role of parents in supporting sports achievement. Data collection techniques use observation, questionnaires, and documentation. Based on the data analysis carried out in the fifth chapter of this thesis, obtained: 1) There are 5 people included in a good category while for the adequate category there are 12 people — of parents’ role in term of attention factor. 2) of parents’ role from nutritional factor, there are 6 people categorized as good while there are 13 people included in adequate category. 3) Parental role from the equipment and supplies factor, there are 2 people included in a good category while 9 people for the adequate category. 4) Environmental factor discussed in parental role problem, both good category and adequate caregory have the same number of people — 8. From this study, we can indicate that the problematic role of parents in supporting sport achievements of Surakarta Women’s Football Club in 2020 which is included in “very poor” category is 4% (1 person), categorized as “less” is 24% (6 people), counted as “adequate” is 36% (9 people), included in “good” is 32% (8 people), and the last but not least “excellent” is 4% (1 person). Based on the average value, which is 101.16, parents’ role in supporting sports achievements of Surakarta U-19 Women’s Football Club in 2020 placed in adequate category.